Payments settlement under limited enforcement: Private versus public systems - Charles M. Kahn; William Roberds (Federal Reserve Bank of Atlanta, 2002)
What are the benefits provided by a payment system? What are the tradeoffs in public versus private payment systems and in restricted versus open payments arrangements? Modern payment systems encompass a variety of institutional designs with varying degrees of counterparty protection. We develop a framework which allows for an examination and comparison of payment systems and specification of conditions leading to their adoption. We relate these conditions to the design of present large-value payment systems (Fedwire, CHIPS, Target, etc.).
Keywords: 330; Payment systems